Effect of Albendazole Treatment in an Experimental Model of Neurocysticercosis-Induced Hydrocephalus - Fogaroli, Marcelo Ortolani; Oliveira, Marcelo Augusto Chiantelli; Filho, Pedro Tadao Hamamoto; Moraes, Marcelo Padovani de Toledo; Vulcano, Luiz Carlos; Bazan, Rodrigo; Zanini, Marco Antônio; Fleury, Agnès (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Hydrocephalus is a major concern in neurocysticercosis (NCC), and its management is more challenging than that of hydrocephalus caused by other etiologies. Even though albendazole is a well-established drug for the treatment of NCC, the death of the parasites may worsen the clinical symptoms and eventually, deteriorate the course of hydrocephalus. The aim of this study was to analyze the effects of treatment with albendazole on the course of hydrocephalus as well as on animal behavior in a rat model of NCC-induced hydrocephalus in order to verify whether the course of hydrocephalus and the animal behavior were changed. Ventricle volumes before and after treatment showed a slight but non-statistically significant difference (168.11 mm3 versus 184.98 mm3, p = 0.45). The distribution and location of the cysts were unaffected. In addition, the behavioral patterns before and after the treatment were not significantly different, as assessed by the open field test. On histologic assessment, mononuclear leukocyte infiltration was present in diverse sites, such as the perivascular and peri-ependymal regions, choroid plexus, and meningeal membranes. A positive correlation was found between the degree of ventricle enlargement and tissue damage. Further studies with long-term comparisons are required.
Keywords: hydrocephalus; neurocysticercosis; albendazole; experimental design